2017
DOI: 10.3892/mmr.2017.6326
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA-451 as a novel hemolytic marker for β0-thalassemia/HbE disease

Abstract: In Southeast Asia, particularly in Thailand, β0-thalassemia/hemoglobin E (HbE) disease is a common hereditary hematological disease. It is associated with pathophysiological processes, such as the intramedullary destruction of immature erythroid cells and peripheral hemolysis of mature red blood cells. MicroRNA (miR) sequences, which are short non-coding RNA that regulate gene expression in a suppressive manner, serve a crucial role in human erythropoiesis. In the present study, the plasma levels of the erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…The role of miRNA genes in normal erythropoiesis [25,26] and globin expression has been demonstrated [1921,27,28]. Therefore, the goal of the present study was to define novel miRNA genes differentially expressed in persons with SCD and contrasting high and low HbF levels.…”
Section: Resultsmentioning
confidence: 98%
“…The role of miRNA genes in normal erythropoiesis [25,26] and globin expression has been demonstrated [1921,27,28]. Therefore, the goal of the present study was to define novel miRNA genes differentially expressed in persons with SCD and contrasting high and low HbF levels.…”
Section: Resultsmentioning
confidence: 98%
“…The normalization of the levels with miR-16 might have been less sensitive to detect variations of less abundant miRNAs. The previous report showed that miR-451, miR-15b and 16 increased with hemolysis [ 19 , 20 , 21 ] suggesting that circulating miR-16 is not suitable internal control in hemolytic condition. We propose that target miRNA-oriented adjustment of the concentration of spiked-in cel-miR-39 is relevant to achieve stable results.…”
Section: Discussionmentioning
confidence: 99%
“…Blood cells are the main origins of circulating miRNAs [ 5 , 15 , 16 ]. Red blood cells contain an erythroid-specific miRNA (miR-451), which is released from old or pathological red blood cells in hemolytic diseases [ 11 , 17 - 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (15) reported that miRNA-451 protected neurons against IRI-induced cell death. Leecharoenkiat et al (16) showed that miRNA-451 levels may be associated with β-thalassemia/hemoglobin-E. The present study aimed to investigate the role of miRNA-451 on cerebral ischemia-reperfusion and its possible mechanism.…”
Section: Introductionmentioning
confidence: 88%